Experimental partitioning of Ca isotopes and Sr into anhydrite: Consequences for the cycling of Ca and Sr in subseafloor mid-ocean ridge hydrothermal systems. (1st September 2018) - Syverson, Drew D.; Scheuermann, Peter; Higgins, John A.; Pester, Nicholas J.; Seyfried, William E.
Abstract: The elemental and isotopic mass balance of Ca and Sr between seawater and the oceanic crust at mid-ocean ridge (MOR) hydrothermal systems integrates various physiochemical processes in the subseafloor, such as dissolution of primary silicate minerals, formation of secondary minerals, and phase separation in the subseafloor. In particular, the precipitation and recrystallization of anhydrite are recognized as important processes controlling the Ca and Sr elemental and isotope composition of high temperature vent fluids and coexisting ocean crust, and yet, little experimental data exist to constrain the mechanism and magnitude of these critical geochemical effects. Thus, this study experimentally examines Sr/Ca partitioning, Ca isotope fractionation, and the rate of exchange between anhydrite and dissolved constituents. These experimental constraints are then compared with Sr/Ca and Ca isotope compositions of anhydrite and vent fluids sampled from the TAG hydrothermal system. Accordingly, anhydrite precipitation and recrystallization experiments were performed at 175, 250, and 350 °C and 500 bar at chemical conditions characteristic of active MOR hydrothermal systems. Experimental data suggest that upon entrainment and recharge of seawater into MOR hydrothermal systems anhydrite will rapidly precipitate with a Ca isotopic composition that is depleted in the heavy isotope compared to the hydrothermal fluid. The magnitude of the Ca isotope fractionation, Δ 44/40 Ca(Anh-Fluid), is temperature dependent, −0.45, −0.22, and −0.02‰, for 175, 250, and 350 °C, respectively, but likely indicative of kinetic effects. Utilization of a 43 Ca spike in solution was implemented to quantify the time-dependent extent of isotope exchange during anhydrite recrystallization at chemical equilibrium. These data indicate that the rate of exchange is a function of temperature, where 12, 46, and 45% exchange occurred within 1322, 867, 366 h at 175, 250, and 350 °C, respectively. The partitioning of Sr/Ca between anhydrite and constituent dissolved species during precipitation depends greatly on the saturation state of the hydrothermal fluid with respect to anhydrite at each experimental temperature, KD(Anh-Fluid) = 1.24–0.55 at 175–350 °C, broadly similar to results of earlier experimental observations by Shikazono and Holland (1983). Equilibrium KD(Anh-Fluid) values were estimated by taking explicit account of time dependent magnitude of exchange, yielding values of 0.43, 0.36, 0.29 at 175, 250, and 350 °C, respectively. Coupling these experimental constraints with the temperature gradient inferred for high temperature MOR hydrothermal systems suggests that the Ca isotope and Sr elemental composition of anhydrite formed near the seafloor will retain the composition derived upon initial formation conditions, which is indicative of disequilibrium. In contrast, at greater depths and at higher temperatures, anhydrite will reflect close to equilibrium Sr/Ca partitioning and Ca isotope fractionation conditions. The experimental and natural data presented in this study can be used to further understand the effect of anhydrite precipitation during hydrothermal circulation in the oceanic crust and on the chemical and isotopic composition of seawater on geologic timescales.